2022
DOI: 10.20452/pamw.16221
|View full text |Cite
|
Sign up to set email alerts
|

Mortality in critically ill COVID-19 patients with fungal infections: a comprehensive systematic review and meta-analysis

Abstract: Among critically ill patients infected with SARS-CoV-2, fungal co-infections may be associated with a significantly higher risk of death. A quantitative analysis of 19 papers showed that COVID-19-associated pulmonary aspergillosis is common and is associated with a threefold higher mortality rate. The prevalence of COVID-19-associated candidiasis appears to be smaller but also linked to mortality.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 45 publications
0
5
0
Order By: Relevance
“…Bacterial and fungal infections are well-known complications of COVID-19 and are significantly associated with poor prognosis [ [134] , [135] , [136] , [137] , [138] , [139] , [140] , [141] ]. A pooled study containing 171 trials with 171,262 patients with COVID-19 discovered that the prevalence of combined bacterial infections was 5.1%, and secondary bacterial infections were 13.1%.…”
Section: Resultsmentioning
confidence: 99%
“…Bacterial and fungal infections are well-known complications of COVID-19 and are significantly associated with poor prognosis [ [134] , [135] , [136] , [137] , [138] , [139] , [140] , [141] ]. A pooled study containing 171 trials with 171,262 patients with COVID-19 discovered that the prevalence of combined bacterial infections was 5.1%, and secondary bacterial infections were 13.1%.…”
Section: Resultsmentioning
confidence: 99%
“…Patients hospitalized in an ICU with severe COVID-19 are at increased risk of developing secondary infections, such as invasive fungal infections [ 63 , 64 ]. This is because they have underlying medical conditions, such as chronic respiratory diseases, and are often treated with corticosteroid therapy and intubation/mechanical ventilation [ 63 , 64 ].…”
Section: Discussionmentioning
confidence: 99%
“…Patients hospitalized in an ICU with severe COVID-19 are at increased risk of developing secondary infections, such as invasive fungal infections [ 63 , 64 ]. This is because they have underlying medical conditions, such as chronic respiratory diseases, and are often treated with corticosteroid therapy and intubation/mechanical ventilation [ 63 , 64 ]. Although there are many reasons for death in critically ill patients with COVID-19, the role of co-infections and their significance are not well understood, with limited research done in this area.…”
Section: Discussionmentioning
confidence: 99%
“…The fatality rate in our research is up to 76.5% and is higher than that reported in the literature. A comprehensive systematic review and meta-analysis found that critically ill patients with CAPA have severely increased mortality, with a median of 54% (IQR 36–70%) in the suspected CAPA group [ 50 ]. In various studies, the mortality ranged from 44.5 to 66.7% to even 100% [ 49 , 51 ].…”
Section: Discussionmentioning
confidence: 99%